Regulating Conscientious Objection to Legal Abortion in Argentina: Taking into Consideration Its Uses and Consequences - Agustina Ramón Michel; Stephanie Kung; Alyse López-Salm; Sonia Ariza Navarrete (Harvard FXB Center for Health and Human Rights, 2020)
Claims of conscientious objection (CO) have expanded in the health care field, particularly in relation to abortion services. In practice, CO is being used in ways beyond those originally imagined by liberalism, creating a number of barriers to abortion access. In Argentina, current CO regulation is lacking and insufficient. This issue was especially evident in the country's 2018 legislative debate on abortion law reform, during which CO took center stage. This paper presents a mixed-method study conducted in Argentina on the uses of CO in health facilities providing legal abortion services, with the goal of proposing specific regulatory language to address CO based not only on legal standards but also on empirical findings regarding CO in everyday reproductive health services. The research includes a review of literature and comparative law, a survey answered by 269 health professionals, and 11 in-depth interviews with stakeholders. The results from our survey and interviews indicate that Argentine health professionals who use CO to deny abortion are motivated by a combination of political, social, and personal factors, including a fear of stigmatization and potential legal issues. Furthermore, we find that the preeminent consequences of CO are delays in abortion services and conflicts within the health care team. The findings of this research allowed us to propose specific regulatory recommendations on CO, including limits and obligations, and suggestions for government and health system leaders.